Gestational hypertension and the risk of preeclampsia (Research, Society and Development, 2022)
Introduction: Gestational hypertension is one of the most prominent diseases when pregnancy is at high risk. It is among the Gestational Hypertensive Syndromes (SHG) for grouping several diseases linked to hypertension. Within the SHG, preeclampsia or specific hypertensive disease of pregnancy (DHEG) deserves special attention, as it occurs as an isolated form or associated with chronic arterial hypertension. Objective: To understand the possible factors that influence preeclampsia in the health care of pregnant women. Methodology: Integrative Literature Review carried out through an exploratory and descriptive applied research. The Virtual Health Library (VHL) portal was used. The research was carried out between November 2021 and April 2022. To search for articles, the Boolean operator “AND” and the following descriptors were used: “primary care”, “pre-eclampsia”, “hypertension”. Results: After applying the selection criteria, the final sample had six (06) articles that were included in the review. The articles selected for the review were hosted in the following databases: MEDLINE (4); LILACS (01); BDENF – Nursing (01). Regarding the language of publication: English (04) and Portuguese (2). Regarding the years of publication of articles, the following results were obtained: 2021 (1); 2020 (2); 2018 (2); 2017 (1). Final Considerations: Among the factors that trigger preeclampsia, the most cited were wrong or late diagnosis, age, ethnicity and the appearance of multiple pregnancies and eating habits. There is a need for a consolidated assistance model for patients at risk of pregnancy-induced hypertension and, consequently, preeclampsia, which can reduce the number of deaths with defined causes.